2006
DOI: 10.1097/01.mlr.0000199692.78295.7c
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Pocket Health Spending Between Low- and Higher-Income Populations

Abstract: Health insurance may not prevent people from having high health care spending. Low-income people with serious health needs appear to be financially constrained and spend less on health care relative to higher-income people, and the presence of health maintenance organizations may help reduce out-of-pocket health care spending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 12 publications
0
52
1
Order By: Relevance
“…At the end of 1996, the experiment reform was extended to 57 other cities, and in December 1998 the government called for reform of the existing GIS and LIS in China's remaining cities. By the end of 2003, the vast majority of large cities had implemented 2 Waters et al (2004), Shen andMcFeeters (2006) andO'Donnell et al (2005) look at the impacts of insurance on a binary variable capturing especially large spending. None, however, captures the endogeneity of insurance.…”
Section: Health Insurance In China-some Salient Factsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of 1996, the experiment reform was extended to 57 other cities, and in December 1998 the government called for reform of the existing GIS and LIS in China's remaining cities. By the end of 2003, the vast majority of large cities had implemented 2 Waters et al (2004), Shen andMcFeeters (2006) andO'Donnell et al (2005) look at the impacts of insurance on a binary variable capturing especially large spending. None, however, captures the endogeneity of insurance.…”
Section: Health Insurance In China-some Salient Factsmentioning
confidence: 99%
“…Often these are tabulations of spending by insurance status or cross-section regressions of spending on insurance status and other covariates: examples from the US, which find higher out-of-pocket spending among the insured, include Rubin and Koelln (1993), Waters et al (2004) and Shen and McFeeters (2006). 1 Such studies are vulnerable to biases caused by health insurance being endogenous.…”
Section: Introductionmentioning
confidence: 99%
“…To date, though, only a few studies (e.g. Sesma-Vazquez et al 2005;Shen and McFeeters 2006;Habibov 2010;Okunade et al 2010; Amaya Lara and Ruiz Gomez 2011) have investigated factors associated with out-of-pocket expenditures (OOPE) and catastrophic expenditures (CE). Also, none of the previous studies examined the issues of OOPE and CE in the Iranian health care system.…”
Section: Introductionmentioning
confidence: 98%
“…This argument is unquestionably correct; however, our study suggests that the overall broader coverage generally available through an employment group is more in line with the needs of individuals who, because of their health conditions, enroll in high-risk pools. Shen and McFeeters (2006) found that regardless of income levels, adults with private, nongroup coverage had the highest risk of incurring high out-of-pocket expenses (. $2,000/year) and bearing a high financial burden (out-of-pocket costs exceeding 5% of income).…”
Section: Discussionmentioning
confidence: 99%